Shining a Light: A Single Case Study of Shine Literacy and the Implementation of their Literacy Interventions During the COVID-19 Pandemic - Houliston, Kate (Department of Sociology, 2024)
This qualitative empirical study is a single case study which considers how the implementation of literacy programmes run by Shine Literacy were affected by the COVID-19 pandemic in 2020-2021. The pandemic necessitated a rapid re-imagining of Shine Literacy's programmes and presented the opportunity for Shine to critically reflect on their interventions. The findings show that the disruption challenged Shine to implement literacy learning in more inclusive and equitable ways, particularly in their recognition of South Africa's stark digital divide. This research incorporated documentary analysis with semi-structured interviews to better comprehend the nuances of the role played by NGOs during the pandemic. The theoretical framework incorporates a socio-cultural approach to literacy and Epstein's (2009) framework which speaks to the overlapping nature of the three spheres of influence in children's education: schools, families, and communities. This study highlights the integral role played by caregivers in literacy learning and accounts for the heterogenous learning experiences of learners during school closures. The implementation of Shine's altered literacy interventions positioned the home as a pedagogical site and caregivers as co-educators. This shift in approach to literacy is both crucial and significant in light of school closures during the pandemic, where a departure from exclusively valuing school-based education was necessary. Based on the findings of how Shine continued to facilitate Foundation Phase literacy learning in households during the pandemic, this study presents a framework of reflection, adaptation, and collaboration (RAC). When framed through the lens of the RAC framework, Shine's model of literacy during the pandemic, which not only increased in scope but generated a model of intervention that was better aligned with the needs of their beneficiaries, shows immense transformative potential as an organisation. This study presents the optimistic perspective that Shine Literacy's transformative potential could serve as an encouraging example to other stakeholders in education. Thinking of literacy in more inclusive and equitable ways has the potential to extend beyond Shine and the pandemic, perhaps even to the low literacy levels and long-standing educational inequalities in South Africa.